2018
DOI: 10.21649/akemu.v23i4.2197
|View full text |Cite
|
Sign up to set email alerts
|

First Experience of Implementation of Kangaroo Mother Care in Punjab- Pakistan to Reduce Morbidity and Mortality in Preterm Infants

Abstract: The study was planned to assess the effect of Kangaroo Mother Care on preterm and stable neonates in reducing neonatal morbidity and mortality. This is a case series design of 121preterm and low birth weight neonates, weighing less than 2500 gram, enrolled from 1 August 2016 till31 January 2017.Kangaroo Mother Care is initiated after birth, after performing early essential newborn care practices. Weight gain of 20-30 gram for three consecutive days, establishment of breast-feeding for 20-30 minutes every two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…No Efficacy [25]. Other researchers from Pakistan have also proposed strengthening of KMC services in local healthcare settings as it can possibly reduce neonatal morbidity and mortality among preterm infants [26,27].…”
Section: (299%) Efficacymentioning
confidence: 99%
“…No Efficacy [25]. Other researchers from Pakistan have also proposed strengthening of KMC services in local healthcare settings as it can possibly reduce neonatal morbidity and mortality among preterm infants [26,27].…”
Section: (299%) Efficacymentioning
confidence: 99%
“…Multiple studies have proved that KMC is associated with improved rates of breast feeding. According to one study, KMC was associated with 4.1 times increase in breastfeeding rate 24 25. Further studies examining breastfeeding outcomes showed that daily volume of milk for babies managed by KMC was 640 mL vs 400 mL for babies managed in incubators 26.…”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…10 Local data from Lahore found KMC to result in decline in morbidity and mortality rates among neonates during NICU stay. 11 Conventional care of LBW neonates is costly and require skilled support and logistic assistance whereas interventions like KMC are not widely used at all healthcare settings. Limited literature is available showing effectiveness of KMC at NICU settings so the present study was aimed at finding out the outcome of intermittent KMC in terms of weight-gain among low birth weight neonates in NICU.…”
Section: Introductionmentioning
confidence: 99%